AN ANALYSIS OF TEACHING LEARNING NARRATIVE WRITING AT THE SECOND YEAR OF SMP MUHAMMADIYAH 2 NGAWI - NASIKHAH, NUR (2010)
This research aims at describing, (1) the implementation of teaching English writing narrative, (2) the difficulties faced by the students and the problem faced by the teacher in teaching writing narrative. In achieving the objectives of the research, the writer conducted observation as the approach to collect and analyze the data. The research is a descriptive qulitative study. The object of the study is the English teaching learning narrative writing at the second year of SMP Muhammadiyah 2 Ngawi. The methods of collecting data of this research are: (1) observation, (2) interview, and (3) test, (4) documentation. In analyzing the data, the writer uses an interactive model. It consists of three main components: (1) reducing of the data, (2) presenting the data, (3) conclusion and verivication. The results of the research show that first, the implementation achieved by the students showed that they are more interested in writing of narrative; the material makes the students able to follow the lesson without any problems. In teaching writing at SMP Muhammadiyah 2 Ngawi the teacher applies four cycles as follows: 1) Building Knowledge of Field (BKOF), 2) Modelling of Text (MOT), 3) Join Construction of Text (JCOT). 4) Independent Construction of Text (ICOT). The teacher gives a clear explanation about the material to create a narrative text. Teacher uses a simple material for the students in junior high school level. And also the teacher gives a question answer for the students to improving of their thinking and idea. Second, the writer found three difficulties faced by English students and teaching English at junior high school. (1) the student difficulty to make a sentence and paragraph so they can't wrote narrative texts for better. (2) the students difficulty uses to grammar so their sentence wrong still. They can't different between past tense and present tense. (3) the students doesn't understand about giving material by the teacher. Third, the writer found three problems that were faced by the English teacher and teaching English at junior high school level especially in the second year. (1) the teacher gets difficulty by the students to receive information about the topic in the teaching English narration at second year level. (2) the teacher got difficulty to build students memorization in memorizing the new vocabulary. (3) the teacher gets difficulty to handle the lazy students, such as the student doesn't exam and homework; make the classroom is not active or passive.